2022
DOI: 10.3389/fpsyg.2022.905862
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Servant Leader and Interpersonal Trust in Predicting Employee-Based Brand Equity: Moderating Role of Ethical Work Climate

Abstract: Although servant leadership may be equipped to provide a leadership model that addresses the issues of the modern workforce, little literature is available regarding the relationship between servant leadership and employee brand-based equity. This study contends to address this gap for which data have been collected from the service industry under a cross-sectional research design by distributing 410 questionnaires among the participants, out of which 337 were received back. After discarding the partially fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Ghafoor et al (2019) found that project governance played a key role in amplifying the impact of benefits management on project success. Furthermore, Zwikael and Smyrk (2015) have suggested that the most effective governance technique in a stable project environment is for the project owner to have control over the project management process. We thus propose that:…”
Section: The Moderating Role Of Project Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Ghafoor et al (2019) found that project governance played a key role in amplifying the impact of benefits management on project success. Furthermore, Zwikael and Smyrk (2015) have suggested that the most effective governance technique in a stable project environment is for the project owner to have control over the project management process. We thus propose that:…”
Section: The Moderating Role Of Project Governancementioning
confidence: 99%
“…During a project, project leaders should display positive behaviors, such as empowerment, support, and people centric, as these behaviors are likely to foster project team members' growth and development. In the workplace, promoting interpersonal trust can encourage and develop positive behaviors such as commitment, engagement, and job satisfaction (Zhang & Guo, 2022). Project managers, being serving in nature, may enhance interpersonal trust by instilling confidence in team members through competence, integrity, fairness, and benevolence (Chan & Mak, 2014;Colquitt et al, 2007;Hartman, 2002), which will enable them to work with determination and dedication to achieve team goals (Bilal et al, 2020).…”
Section: Managerial Implicationsmentioning
confidence: 99%